2010
DOI: 10.1108/01443581011061267
|View full text |Cite
|
Sign up to set email alerts
|

Trade linkages between China, India and Singapore

Abstract: Purpose -The purpose of this paper is to examine the trade linkages and degree of export competitiveness between Singapore, China and India. Design/methodology/approach -Balassa's export performance index and the dynamic RCA index was adopted, as suggested by Kreinin and Plummer to identify the revealed comparative advantage (RCA) of the above countries in industrial products by SITC 1-and 2-digit levels. The Spearman's rank correlation coefficient is used to identify the degree of complementarity between RCA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 13 publications
(11 reference statements)
0
8
0
Order By: Relevance
“…States that the higher the price is set, the amount of demand will decrease. An increase in export prices in the destination country tends to result in a decrease in the quantity of the commodity demanded (Jayawickrama & Thangavelu, 2010). However, because the results show that the price does not have a significant relationship with the level of Indonesian potato exports to Malaysia, changes in the export price of export potatoes do not have much effect on the level of export.…”
Section: Resultsmentioning
confidence: 76%
“…States that the higher the price is set, the amount of demand will decrease. An increase in export prices in the destination country tends to result in a decrease in the quantity of the commodity demanded (Jayawickrama & Thangavelu, 2010). However, because the results show that the price does not have a significant relationship with the level of Indonesian potato exports to Malaysia, changes in the export price of export potatoes do not have much effect on the level of export.…”
Section: Resultsmentioning
confidence: 76%
“…Analysis was performed using the "Diamond Model", where raw materials, labor, capital, demand, related industries, strategies and policies were included as explanatory variables, and the impact of international competitiveness on market share (MS), trade competitiveness (TC) and comparative advantage (RCA) Research findings imply that it is necessary to increase investment in the fixed assets of the Chinese textile and apparel industry, accelerate the pace of equipment upgrading, increase the rate of industrialization, while strengthening the supply of textile raw materials, and reduce raw material prices, thereby reducing company costs textiles and apparel. (Jayawickrama & Thangavelu, 2010) Test trade relations and the level of export competitiveness between Singapore, China and India. The Balassa export performance index and dynamic RCA index were adopted to identify revealed comparative advantages (RCA) from Singapore, China and India in industrial products with 1 and 2 digit SITC levels.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The Balassa export performance index and dynamic RCA index were adopted to identify revealed comparative advantages (RCA) from Singapore, China and India in industrial products with 1 and 2 digit SITC levels. (Jayawickrama & Thangavelu, 2010) found that exports of Singapore and China complement each other, even though the level of complementarity has declined over time. Meanwhile, Singapore and India exports were found to be a stronger and more stable complement.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The study indicated that trade structures and processes between China, India and Singapore should be complementary due to the existence comparative advantages. Though India had some comparative advantages in a large category of products, it should complement with other countries (Jayawickrama & Thangavelu , 2010). This means that even if urban centres think that they have comparative advantages in many products than rural people, they should engage in trade to complement each other.…”
Section: Business and Economic Researchmentioning
confidence: 99%